Effect of Gadung Tuber Extract (Dioscorea hispida) on Mortality of Caterpillars (Spodoptera exigua) in Shallots (Allium cepa) in East Lombok - Muhammad Mustarsidin; Syachruddin AR; Ahmad Raksun (Jurnal Biologi Tropis, 2020)
Plants that can be used as pesticides are Gadung tubers. Gadung tubers contain cyanide acid to kill armyworm pests because they contain dioscorin toxins which can cause nervous disorders. The purpose of this study was to determine the effect of Gadung tuber extract (Dioscorea hispida) on Caterpillar mortality (Spodoptera exigua) in Shallot plants. This type of research is experimental research. This study used a completely randomized design (CRD). The sample used was 5 caterpillars (Spodoptera exigua) in each polybag with 5 repetitions for each concentration of Gadung tuber extract, namely 0%, 0.5%, 1.0%, 1.5%, 2.0% and 2.5%, so the total Caterpillar used was 150 Caterpillars. Gadung tuber extraction was carried out by maceration method with methanol solvent. Data were analyzed using a one-way analysis of variance at the 95% significance level, followed by DMRT (Duncans Multiple Range Test). The results showed that the Gadung tuber extract had a significant effect on the mortality of caterpillars (Spodoptera exigua) because the F count was greater than the F table (45.40>2.62), and the DMRT test results showed that the optimal concentration of Gadung tuber extract was 2.5%. Therefore, it can be concluded that the extract of Gadung tuber (Dioscorea hispida) affects the mortality of Caterpillars (Spodoptera exigua) in Shallots (Allium cepa).